Internalisasi Karakter Santri Melalui Pembelajaran Tari Zapin Berbasis Community Based Learning di Grup Zapinestars Pondok Pesantren Cipasung Kabupaten Tasikmalaya - Tania Rahmawati Hidayat; Asti Tri Lestari; Wan Ridwan Husen (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study aims to describe the learning process of Zapin Dance based on the community and to identify the character values of students that are internalized through this learning practice. Art activities in pesantren are generally positioned as the development of interests and talents, so the learning experiences and social experiences within them have not been fully understood as part of the character education process. The research uses a descriptive qualitative approach with observation, interview, and documentation techniques. Community Based Learning (CBL) is used as an analytical framework to study learning practices that naturally occur within the Zapinestars community. The results of the study indicate that learning takes place in a non-formal, gradual, and participatory manner through social interaction, habitual practice, cooperation, and collective responsibility. Character values such as discipline, responsibility, cooperation, social care, and manners are evident through the behavior and habits of the students during the training process. These findings confirm that Zapin Dance functions not only as an art activity but also as a social learning space that allows the internalization of character to take place through real experiences within the community.